Integrated tools for improving the resilience of seaports under extreme wind events. (July 2017) - Repetto, M.P.; Burlando, M.; Solari, G.; De Gaetano, P.; Pizzo, M.
Abstract: This paper describes a set of integrated tools that include a high quality monitoring network and an innovative forecasting system for the safe management and risk assessment of seaports under extreme wind events. It furnishes operative data for the real-time remote control of docks, weather forecasting for daily activity management and emergency alert under extreme events, and statistical info for the strategical and long-term design and management of port areas. The performance of this system is critically discussed considering some selected intense weather events. The results point out its merits and also some defects in predicting such events with a satisfactory approximation both in intensity and time evolution, thus providing Port Authorities with basic information to manage both the safety issues during the adverse weather conditions and timely return to normal operating capacity, increasing the resilience of the involved seaports. This system may represent a reference model for improving the resilience of any structural, infrastructural and territorial system.